Variance Premium and Implied Volatility in a Low-Liquidity Option Market* - Astorino, Eduardo Sanchez; Chague, Fernando; Giovannetti, Bruno; Silva, Marcos Eugênio Da (Fundação Getúlio Vargas, 2017)
We propose an implied volatility index for Brazil that we name IVol-BR. The index is based on daily market prices of options over Ibovespa-an option market with relatively low liquidity and few option strikes. Our methodology combines standard international methodology used in high-liquidity markets with adjustments that take into account the low liquidity in Brazilian option markets. We do a number of empirical tests to validate the IVol-BR. First, we show that the IVol-BR has significant predictive power over future volatility of equity returns not contained in traditional volatility forecasting variables. Second, we decompose the squared IVol-BR into (i) the expected variance of stock returns and (ii) the equity variance premium. This decomposition is of interest since the equity variance premium directly relates to the representative investor risk aversion. Finally, assuming Bollerslev, Tauchen, & Zhou (2009) functional form, we produce a time-varying risk aversion measure for the Brazilian investor. We empirically show that risk aversion is positively related to expected returns, as theory suggests.

Nós propomos um índice de volatilidade implícita para o mercado acionário do Brasil que chamamos de IVol-BR. O índice é baseado nos preços diários das opções sobre o Ibovespa-um mercado de opções com liquidez relativamente baixa e poucos preços de exercício. Nossa metodologia combina a metodologia internacional padrão usada em mercados de alta liquidez com ajustes que levam em conta a baixa liquidez do mercado brasileiro. Conduzimos uma variedade de testes empíricos a fim de validar o IVol-BR. Em primeiro lugar, demonstramos que o IVol-BR possui um poder de previsão significativo sobre a volatilidade futura do retorno do Ibovespa que não é encontrado em variáveis de previsão de volatilidade tradicionais. Em segundo lugar, decompomos o quadrado do IVol-BR em (i) a variância esperada do retorno e (ii) o prêmio de variância. Essa decomposição é de interesse porque o prêmio de variância se relaciona diretamente com a aversão a risco do investidor representativo. Finalmente, assumindo a forma funcional de Bollerslev, Tauchen, & Zhou (2009), produzimos uma medida de aversão a risco variante no tempo para o investidor brasileiro. Mostramos empiricamente que essa aversão a risco é positivamente correlacionada com os retornos esperados, como a teoria sugere.
Keywords: Volatility Index; Predictability; Risk Aversion; Equity Variance Premium